Frailty measurement and outcomes in interventional studies: protocol for a systematic review of randomised control trials. Issue 12 (26th December 2017) - Shears, Melissa; McGolrick, Danielle; Waters, Braden; Jakab, Marnie; Boyd, J. Gordon; Muscedere, John
Abstract : Introduction: Frailty is associated with reduced functional capacity, decreased resistance to stressors and is predictive of a range of adverse health outcomes, including dependency, hospitalisation and mortality. Early identification of frailty may prevent, reduce and postpone adverse health outcomes. However, there is a need for additional evidence to guide decision-making for the care of frail patients since frail persons are frequently excluded from studies, the differential impact of frailty is often not examined in clinical trials and few large-scale clinical trials examining frail cohorts have been conducted. Randomised control trials (RCTs) published to date have used a diverse range of definitions of frailty, as well as a variety of outcome measures. The objective of this systematic review is to comprehensively characterise the frail populations enrolled and the end points reported in frailty RCTs. Methods and analysis: We will identify all RCTs reporting on the outcome of interventions in adult (age ≥18 years) frail populations as defined by authors, in all settings of care. Databases will include MEDLINE, CINAHL, EMBASE, PsycInfo, Global Health, the Joanna Briggs database and Cochrane Library. Two reviewers will independently determine trial eligibility. For each included trial, we will conduct duplicate independent data extraction, inter-rater reliability, risk of bias assessment and evaluation of the quality of the evidence using the Grading of Recommendations, Assessment, Development and Evaluations approach. Ethics and dissemination: This systematic review will comprehensively identify RCTs including frail patients to identify how frailty is measured and which outcomes are reported. The results of this systematic review may inform clinicians caring for persons with frailty, facilitate conduct of future RCTs and inform future efforts to develop common data elements and core outcomes for frailty studies. Our findings will be disseminated through conference presentation and publication in peer-reviewed journals. PROSPERO registration number: CRD42017065233 .